Morphological and Morphometric Variations of Lantern Shell Lingula anatina from Madura Strait, East Java, Indonesia - Rakmawati; Gafur, Abdul (LenteraBio : Berkala Ilmiah Biologi, 2025)
Lingula anatina is an ancient invertebrate that still exists and has not experienced shell morphological evolution since the Silurian period. Lingula anatina lives burrowing in sand to mud substrates in mangrove ecosystems. This study aims to describe the morphological and morphometric variations of L. anatina that found in Madura Strait, East Java. Sampling was carried out using the purposive sampling method by digging the substrate in the plot area to a depth of 5-10 cm. Morphological characters were analyzed based on shell shape, while five morphometric profiles were analyzed using the Principal Component Analysis (PCA) method using PAST software version 4.12. The results showed that three morphological variations of L. anatina were found. Meanwhile, L. anatina is known to have morphometric profiles in varying data ranges. This study also found anomalies occurrences or records in three individuals of L. anatina.